Apexification post traumatic injury-a case report - Ardini, Yunita Dewi (2011)
Dentoalveolar trauma in children often cause distress for both children and parents and also difficult for the dentist. Trauma is one of the most common presentations of young children to a Pediatric dentist. Incomplete formed apex causes a significant problem during management for children. Present case came with fractured maxillary central incisor with pulp exposure. The case was managed with apexification using calcium hydroxide. calcium hydroxide is most commonly used to induce an apical hard tissue barrier. Material of choice is discussed. The aim of this treatment is to create an apical hard tissue barrier by using calcium hydroxide which the root canal filling can be placed.